Establishing a system for measuring the organizational performance of a node of the associative network of African athletics - LANHA, MAGLOIRE BONAVENTURE JOSEPH; AKOUETE, Coffi DAVID; SAIDOU, Victor (My University, 2020)
This article conceives a system of evaluation of the organizational performance of a node of the associative network objective have been developed and integrated into a performance construct of a network entity. The developed measurement system assesses the organizational performance of the baseline activity forecasts perceived by the network's top. It is likely to constitute the frame of a physical computing medium that can generate objective values different from the sports results in force for evaluation purposes of this network.
Keywords: Organizational Performance; Performance Indicator; Evaluation; System; ECOGRAI; African Athletics.